Model Pembelajaran Deep Learning dalam Mendukung Kurikulum Merdeka - Harjun Harjun; Murni Nia; Suci Ramadhani (Indo Publishing, 2026)
This study aims to determine the application of the Deep Learning Model in Supporting the Independent Curriculum. This study employed the Systematic Literature Review (SLR) method. Researchers identified 20 relevant journals discussing the deep learning model in support of the Independent Curriculum. This systematic review of 20 scientific journals collectively demonstrates that deep learning is not merely a trend, but rather a pedagogical approach with a strong empirical basis for supporting the implementation of the Independent Curriculum in Indonesia. This approach has been proven to improve the quality of learning by strengthening students' critical thinking skills, creativity, motivation, and conceptual understanding.